MRI of foetal development - Anblagan, Devasuda (2012)
Foetal MRI represents a non-invasive imaging technique that allows detailed visualisation of foetus in utero and the maternal structure. This thesis outlines the quantitative imaging techniques used to investigate the effect of maternal diabetes and maternal smoking on foetal development at 1.5 Tesla. The effect of maternal diabetes on placental blood flow and foetal growth was studied. The placental images were acquired using Echo Planar Imaging and blood flow was measured using Intra Voxel Incoherent Motion. The results indicate that peak blood flow in the basal plate and chorionic plate increases across gestation in both normal and diabetic pregnancies. Conversely, diffusion in the whole placenta decreases across gestation, with a more pronounced decrease in diabetic placentae. Following this, a method was developed to use a Tl weighted fat suppressed MRI scan to quantify foetal fat images in-utero. In addition, HAlf Fourier Single-shot Turbo spin Echo (HASTE) and balanced Fast Field Echo (bFFE) were used to acquire images encompassing the whole foetus in three orthogonal planes. These scans were used to measure foetal volume, foetal length and shoulder width. The data shows that foetal fat volume and intra-abdominal fat were increased in foetuses of diabetic mothers at third trimester. The HASTE and bFFE sequences were also used to study the effect of maternal smoking on foetal development. Here, foetal organ volumes, foetal and placental volume, shoulder width and foetal length were measured using a semiautomatic approach based on the concept of edge detection and a stereological method, the Cavalieri technique. The data shows that maternal smoking has significant negative effect on foetal organ growth and foetal growth, predominantly foetal kidney and foetal volume. The work described here certainly has a great potential in non-invasive assessment of abnormal placental function and can be used to study foetal development.